A Framework of Global e-Learning for the Advanced Generations - Miah, Md. Rahimullah (Asian Business Review, 2012)
This paper explores a predicted framework for global e-Learning that emphasizes the transformative interaction among the effective individuals around the regional, national and global networking indicating advancement on pedagogical models, instructional strategies, and learning technologies in the context on upcoming generations. We have to develop the framework on global enhanced teaching and effective e-Learning to fulfill the required method, implementing design and appraising the feedback with educational technology according to topological network for disseminating of global education technology. Despite decades of development, electronic teachers still need practical examples of how to use electronic educational technology within a pedagogically effective way including electronic curricula, language tools and electronic facilitators. We present a theoretical framework for our representation method, taking into account previous models and characteristics of an effective e-Learning. In addition, we illustrate the course that we have to develop and implement among the participants in this expected model. We follow this with an evaluation of achievement, both in the course implementation and the amplitude framework. Finally, we focus advanced research trajectories of the model and recommendations for how to further develop the route.
Keywords: E-Learning; Transformative Interaction; Teaching Pedagogy; Education Technology